Sharing Experiences over Video: Watching Video Programs Together at a Distance - Macaranas, Anna; Venolia, Gina; Inkpen, Kori; Tang, John (Proc. INTERACT 2013, 2013)
While video communication is becoming quite popular among remote friends and family, recent usage practices have been extending beyond just talking heads to remotely sharing an experience by doing an activity together. However, current video chat tools are aimed at sharing talking heads and need to be reconsidered to support remotely sharing activities. We explore a specific remote shared activity – watching video programs – through a three-phase study. We surveyed people’s interest in watching video together, studied how people currently watch together in their homes, and compared different conditions for watching together in the lab. Our work explored people’s current and desired practices, interactions, and technical implementations. We present our findings in themes that provide in-sights for designing systems that better support using video-mediated communication to share watching videos together over distance. We found that remotely watching video programs together while connected by video-mediated communication is engaging, fun, and fosters social bonds between the participants, and that these results are stronger with increased fidelity of the communication media.